2018
DOI: 10.1109/jlt.2018.2866832
|View full text |Cite
|
Sign up to set email alerts
|

Optical Injection-Locked Directly Modulated Lasers for Dispersion Pre-Compensated Direct-Detection Transmission

Abstract: The growing traffic demand in interdata center and metro communications requires high-speed and low-cost transceivers that can flexibly adapt to different transmission distances of up to a few hundred km. Ultimately low-cost transceivers will use the simplest optical hardware, namely a directly modulated transmitter and direct detection receiver. Using optical injectionlocked directly modulated lasers, we propose a transmitter that can control the full field of the optical signal and achieve errorfree transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Using this transmitter, we generated CDprecompensated signals and achieved 300-km transmission of PAM4 signal without using any dispersion compensation fiber [78]. In principle, the used transmitter-side DSP allows for compensation of all linear transmission impairments (on the top of the demonstrated CD)).…”
Section: B Coherent Transmitter Based On Dmlmentioning
confidence: 99%
“…Using this transmitter, we generated CDprecompensated signals and achieved 300-km transmission of PAM4 signal without using any dispersion compensation fiber [78]. In principle, the used transmitter-side DSP allows for compensation of all linear transmission impairments (on the top of the demonstrated CD)).…”
Section: B Coherent Transmitter Based On Dmlmentioning
confidence: 99%
“…It has been shown that OIL can significantly enhance small-signal modulation BW by more than threefold [13] and suppress modulation chirp, leaving very small residual chirp that depends on the injection ratio (or the locking range). The suppressed chirp offers a unique opportunity of generating arbitrary amplitude-phase modulated signals through coherent synthesis of two or more DMLs [6,14]. The main challenge of OIL is how to integrate multiple independent lasers with isolator or circulator in between.…”
Section: Optical Injection Lockingmentioning
confidence: 99%
“…For the above-mentioned reasons, OIL DM lasers are currently the focus of intensive research as a promising option for application in advanced systems. [13][14][15][16] One of the very recent developments is utilization of the OIL technique in THz emitters, 17 with experimental demonstration of a dramatic decrease in the linewidth and noise component of the emission power spectrum under OIL conditions.…”
Section: Introductionmentioning
confidence: 99%